Long-term impacts of Chromolaena odorata (L.) invasion and ungulate grazing on ant body size and communities in Hluhluwe-iMfolozi Park, South Africa - Somers, Michael J. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.